Substitution Method

fc1123

New member
Joined
Feb 4, 2010
Messages
16
I am having a problem of where to begin here's the problem:

4x-3y=-9
-4x -4x-9
so I got -3y=-9 but from there I am not sure where to go from there.

x-y=-3
 

Denis

Senior Member
Joined
Feb 17, 2004
Messages
1,465
Substitution involves 2 equations. You posted one only: want us to guess or something?

What grade are you in? Attend math classes?
 

fc1123

New member
Joined
Feb 4, 2010
Messages
16
Ok the equation is

4x-3y=-9

x-y=-3
 

Denis

Senior Member
Joined
Feb 17, 2004
Messages
1,465
fc1123 said:
Ok the equation is
4x-3y=-9
x-y=-3
x - y = -3 : then x = y - 3
Substitute that in 1st equation and solve.
If you can't, you need classroom help.
 
Top